The play and the invention of the world in Walter Benjamin and Donald Winnicott (Psicologia USP, 2016)
This study focuses on the play, and uses the fundamental importance of this act for the development of the individual and of culture. This is a theoretical research, which uses discussion and concept articulation of playing present in Walter Benjamin and Donald Winnicott. It starts with an introduction to Winnicott, then putting his line of thought in dialogue with some of Benjamin's ideas about play. Both authors emphasize the importance of the play in culture and evidence its psychological dimension. The transitional phenomena of Winnicott and the similarities doctrine of Benjamin point to the moment when cultural, historical and psychological conditions are created for the invention of the worlds we come to live in.